Teaching history with film - Marcus, Alan S., author.
1 online resource (232 pages)
Keywords: Teaching History with Film provides a fresh, engaging, and clear overview of teaching with film to effectively enhance social studies instruction. Using cases of experienced teachers to illustrate accomplished history teaching through movies, this text provides pre- and in-service teachers with ideas for implementing film-based lessons in their own classrooms and offers a deeper understanding of the thorny issues involved in using film to teach history. The second edition is completely revised and updated including: two entirely new case studies; a new chapter focusing on using international film and incorporating a more global view in the classroom; and additional material on using film to tackle difficult and controversial issues; as well as updates to all of the cases. Discussion of the practical considerations facing classroom teachers, including juggling time restraints, issues of parental permission, and meeting standardsEach section of the book focuses on how teachers can effectively support the development of students’ historical film literacy through topics such as using film to develop interpretive skills, to explore controversial issues, and to develop historical empathy. By developing the skills students need to think critically about the past or what they think they know about history, the lessons in this book illustrate how to harness the pedagogical power of film to provide the tools necessary for rigorous inquiry and democratic citizenship.Reflection on the Case, following each chapter, analyzing and discussing the strengths and limitations of the teacher’s approach as well as providing strategies for using and choosing films specific to the educational outcomeSample unit outlines, descriptions of class texts and films, worksheets, essay questions, viewer guides, and exercises for the classroom throughout.